A solid electrolyte and its preparation method and battery

Through high-pressure synthesis technology, the problems of complex atmospheric synthesis process and product impurities are solved, and the high performance and singularity of solid electrolytes are achieved, which is suitable for the development of all-solid lithium-ion batteries.

CN116986904BActive Publication Date: 2025-04-25SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310845878.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-04-25
Estimated Expiration
2043-07-11

AI Technical Summary

Technical Problem

In the prior art, the atmospheric pressure synthesis technology is complex, and the synthetic products always contain impurities, making it difficult to obtain a single target product, which affects the performance of the solid electrolyte.

Method used

High-pressure synthesis technology is adopted to shorten the distance between lithium ions, improve the ionic conductivity of the electrolyte, and synthesize solid electrolytes under high temperature and high pressure conditions to ensure the singleness and high purity of the product.

Benefits of technology

It realizes the high ionic conductivity and good electrochemical stability of solid electrolytes, simplifies the process flow, reduces the generation of impurities, and improves the singleness and performance of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116986904B_ABST
    Figure CN116986904B_ABST
Patent Text Reader

Abstract

The present application relates to a solid electrolyte and a preparation method thereof and a battery, belonging to the technical field of solid electrolytes. A solid electrolyte, whose chemical formula is (Li r X a )(B s Y b )(S t Z c ); wherein X is selected from any one of Na, K, Mg, Ca, Al and Fe; Y is selected from any one of Si, Al, P, Ga and Ge; and Z is selected from any one of O, Se, F, Cl, Br and I. The solid electrolyte provided in the present application has four crystal forms, each of which is well crystallized, can exist stably under normal pressure, and has good ionic conductivity. The preparation method uses high-pressure synthesis technology to shorten the distance between lithium ions, thereby improving the ionic conductivity of the electrolyte, and the reaction time is short, and the prepared target product is single and has no by-products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solid electrolytes, and in particular to a solid electrolyte and a preparation method thereof and a battery. Background Art

[0002] With the increasing consumption of primary energy such as oil and coal, the storage capacity is gradually decreasing, and renewable energy such as wind energy, solar energy and other secondary energy will gradually replace primary energy. However, due to the discontinuity of these energy sources, it is impossible to continuously supply energy, so an energy storage device is needed to assist in achieving continuous energy supply. The most common way to use renewable energy is to convert it into electrical energy for use, that is, new energy power generation technology, because in today's world, whether it is industrial production or social life, the demand for electrical energy is increasing day by day. It can be seen that the necessary electrical energy storage device plays a vital role in new energy power generation technology. As we all know, the most widely used energy storage method is the battery. Among the many types of batteries, lithium batteries are increasingly widely used in the field of energy storage due to their long life, high specific energy, good discharge, high safety, small size and other advantages. Coupled with policy support, lithium batteries have now become the main development direction in the field of batteries.

[0003] At present, commercial lithium-ion batteries generally use organic liquid electrolytes and gel electrolytes, which inevitably introduce volatile, flammable, and explosive organic liquids into the battery system, bringing serious safety hazards to the battery system. In contrast, solid electrolytes have outstanding advantages in safety, thermal stability, electrochemical stability, etc. Therefore, vigorously developing all-solid-state lithium-ion batteries is the only way to fundamentally solve the battery safety problem. Summary of the invention

[0004] One of the objects of the present invention is to provide a new solid electrolyte.

[0005] To achieve one of the above purposes, the technical solution adopted by the present invention is as follows:

[0006] A solid electrolyte, the general chemical formula of which is shown in formula (I),

[0007] (Li r X a )(B s Y b )(S t Z c ) Formula (I)

[0008] In formula (I), X is selected from any one of Na, K, Mg, Ca, Al and Fe; Y is selected from any one of Si, Al, P, Ga and Ge; Z is selected from any one of O, Se, F, Cl, Br and I;

[0009] In formula (I), the cationic valence of X is m, the cationic valence of Y is n, and the anionic valence of Z is -p;

[0010] r, a, s, b, t, and c satisfy the following conditions respectively:

[0011] 0≤a≤0.5, and r+a≤1;

[0012] 0≤b≤0.5, and s+b≤1;

[0013] 0≤c≤1, and t+c≤2;

[0014] r+ma+3s+nb=2t+pc.

[0015] The solid electrolyte has good crystallization phase, can exist stably under normal pressure, and has good ionic conductivity.

[0016] Developing solid electrolyte materials with excellent performance is an important part of developing all-solid-state batteries, but the atmospheric pressure synthesis technology currently used is complicated, and the synthesized products always have impurities, making it difficult to obtain a single target product. In order to solve the technical problem that the atmospheric pressure synthesis technology used in the prior art is complicated, and the synthesized products have impurities, making it difficult to obtain a single target product, the second purpose of the present invention is to provide a method for preparing a solid electrolyte, which uses high-pressure synthesis technology to shorten the distance between lithium ions, thereby improving the ionic conductivity of the electrolyte, and the reaction time is short, and the prepared target product is single and has no by-products.

[0017] To achieve the second purpose above, the technical solution adopted by the present invention is as follows:

[0018] A method for preparing a solid electrolyte comprises the following steps:

[0019] S1. The initial raw materials are mixed and then ground and pre-pressed to obtain an embryo;

[0020] S2. The embryo in step S1 is synthesized at 1-5 Gpa and above 650° C. to obtain the solid electrolyte, whose general chemical formula is shown in formula (I);

[0021] The initial raw materials include a lithium source, a sulfur source, a boron source, and a general formula of X a Z am / p and Y b Z bn / p One or more of the compounds;

[0022] The lithium source includes one or more of lithium sulfide, lithium iodide, lithium bromide and lithium oxide; the sulfur source includes sulfur powder; the boron source includes boron powder;

[0023] Wherein, X is selected from any one of Na, K, Mg, Ca, Al and Fe; Y is selected from any one of Si, Al, P, Ga and Ge; Z is selected from any one of O, Se, F, Cl, Br and I;

[0024] Among them, the cationic valence of X is m, the cationic valence of Y is n, and the anionic valence of Z is -p;

[0025] r, a, s, b, t, and c satisfy the following conditions respectively:

[0026] 0≤a≤0.5, and r+a≤1;

[0027] 0≤b≤0.5, and s+b≤1;

[0028] 0≤c≤1, and t+c≤2;

[0029] r+ma+3s+nb=2t+pc.

[0030] A third object of the present invention is to provide a solid electrolyte prepared by the above-mentioned preparation method.

[0031] To achieve the third purpose above, the technical solution adopted by the present invention is as follows:

[0032] A solid electrolyte prepared by the above preparation method.

[0033] A fourth object of the present invention is to provide a battery comprising any one of the above-mentioned solid electrolytes.

[0034] To achieve the fourth objective above, the technical solution adopted by the present invention is as follows:

[0035] A battery comprising any one of the above-mentioned solid electrolytes. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1 This is a schematic diagram of the assembly of the pyrophyllite module in the embodiment of the present application;

[0038] Figure 2 This is the X-ray diffraction spectrum in Experimental Example 1 of this application;

[0039] Figure 3These are the ionic conductivity test results of the target products prepared in Examples 1-4 of the present application.

[0040] Icons: 1-metal plug; 2-molybdenum sheet; 3-pyrophyllite; 4-zirconia ring; 5-carbon tube; 6-hexagonal boron nitride tube; 7-blank. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0042] The solid electrolytes that have been reported so far include NASICON-type electrolytes, LISICON-type electrolytes, perovskite-type solid electrolytes, antiperovskite-type solid electrolytes, garnet-type electrolytes and sulfide electrolytes.

[0043] Among all the solid electrolytes studied, sulfides are the most promising electrolyte system due to their highest ionic conductivity, ideal mechanical ductility, and good interface contact with electrodes. Theoretical calculations predict that the Li-BS system may have extremely high lithium ion conductivity and good electrochemical stability, and therefore has great application prospects. However, the atmospheric pressure synthesis technology currently used is complex, and the synthesized products always have impurities, making it difficult to obtain a single target product, so that the system has not made any major breakthroughs.

[0044] The inventors have synthesized a new compound using high temperature and high pressure technology. The chemical formula of the compound is shown in formula (I):

[0045] (Li r X a )(B s Y b )(S t Z c ) Formula (I)

[0046] In formula (I), X is selected from any one of Na, K, Mg, Ca, Al and Fe; Y is selected from any one of Si, Al, P, Ga and Ge; Z is selected from any one of O, Se, F, Cl, Br and I;

[0047] In formula (I), the cationic valence of X is m, the cationic valence of Y is n, and the anionic valence of Z is -p;

[0048] r, a, s, b, t, and c satisfy the following conditions respectively:

[0049] 0≤a≤0.5, and r+a≤1;

[0050] 0≤b≤0.5, and s+b≤1;

[0051] 0≤c≤1, and t+c≤2;

[0052] r+ma+3s+nb=2t+pc.

[0053] The compound satisfying the above chemical formula has good crystal phase, can stably exist under normal pressure, and has good ionic conductivity, and can be used as a solid electrolyte.

[0054] The above chemical formula includes LiBS 2 and a compound in which at least one of the Li position, the B position and the S position is doped with other elements; that is, in LiBS 2 Li-site doping, B-site doping or S-site doping was carried out on the basis of

[0055] In some embodiments, a=b=c=0, and the chemical formula of the solid electrolyte is LiBS 2 .

[0056] In some embodiments, the crystal form of the compound represented by formula (I) is any one of cubic phase, tetragonal phase, hexagonal phase and monoclinic phase. When the compound represented by formula (I) is in pure phase, the ion conductivity is higher. Further, the compound represented by formula (I) is in cubic phase, and the ion conductivity of the cubic phase is several orders of magnitude higher than the ion conductivity of the other three crystal forms.

[0057] The method for preparing the solid electrolyte provided in the embodiment of the present application comprises the following steps:

[0058] S1. The initial raw materials are mixed and then ground and pre-pressed to obtain an embryo;

[0059] S2. The embryo in step S1 is synthesized at 1-5 Gpa and above 650° C. to obtain a solid electrolyte, the general chemical formula of which is shown in formula (I);

[0060] The initial raw materials include a lithium source, a sulfur source, a boron source, and a general formula of X a Z am / p and Y b Z bn / p One or more of the compounds;

[0061] The lithium source includes one or more of lithium sulfide, lithium iodide, lithium bromide and lithium oxide; the sulfur source includes sulfur powder; the boron source includes boron powder;

[0062] Wherein, X is selected from any one of Na, K, Mg, Ca, Al and Fe; Y is selected from any one of Si, Al, P, Ga and Ge; Z is selected from any one of O, Se, F, Cl, Br and I;

[0063] Among them, the cationic valence of X is m, the cationic valence of Y is n, and the anionic valence of Z is -p;

[0064] r, a, s, b, t, and c satisfy the following conditions respectively:

[0065] 0≤a≤0.5, and r+a≤1;

[0066] 0≤b≤0.5, and s+b≤1;

[0067] 0≤c≤1, and t+c≤2;

[0068] r+ma+3s+nb=2t+pc.

[0069] The preparation method utilizes high-pressure synthesis technology to shorten the distance between lithium ions, thereby improving the ionic conductivity of the electrolyte, and the reaction time is short, and the prepared target product is single and has no by-products.

[0070] In some embodiments of the present application, the above raw materials are prepared in a closed container without water or with a trace amount of water to avoid H 2 The generation of harmful gases such as S.

[0071] In some embodiments of the present application, X a Z am / p Including but not limited to Na 2 O, NaCl, NaF, K 2 O, KCl, KF, MgO, MgCl 2 、Al 2 O 3 、AlCl 3 , Fe 2 O 3 、FeCl 3 .

[0072] In some embodiments of the present application, Y b Z bn / p Including but not limited to SiO 2 、SiI 4 、Al 2 O 3 、AlCl 3 , P 2 O 5 .

[0073] In some embodiments of the present application, compound X a Zam / p and Y b Z bn / p different.

[0074] In some embodiments, the grinding conditions include: grinding speed of 400-500r / min, grinding time of 6-10h; within the range of grinding speed and grinding time, the raw materials can be mixed more evenly. And / or, the pre-pressing conditions include: pressure of 60-100MPa; holding time of 1-5min. Pre-pressing is pre-pressed into a cylindrical shape, because the boron nitride and carbon tubes wrapped outside the sample are cylindrical.

[0075] In some embodiments, the grinding time is 6-8 hours.

[0076] In some embodiments, the pre-pressing conditions include: a pressure of 80 MPa; and a holding time of 3 min.

[0077] In some embodiments, the synthesis temperature is 650-1100° C. The target product cannot be synthesized when the temperature is lower than 650° C., and too high a temperature will waste energy, so in some embodiments, the synthesis temperature is 650-1100° C.

[0078] In some embodiments, the crystal form of the compound represented by formula (I) can be cubic at a synthesis temperature of 1000-1100°C; or, the crystal form of the compound represented by formula (I) can be tetragonal at a synthesis temperature of 850-1000°C; or, the crystal form of the compound represented by formula (I) can be hexagonal at a synthesis temperature of 750-800°C; or, the crystal form of the compound represented by formula (I) can be monoclinic at a synthesis temperature of 650-700°C. In order to obtain the corresponding single crystal phase, the synthesis temperature can be selected within the temperature range corresponding to the above crystal phases.

[0079] In some embodiments, the synthesis time is 40-60 min. Within the above synthesis time range, the reaction can be completed.

[0080] The device used for synthesis is mainly to provide a closed environment with set temperature and pressure conditions for the reaction. In some embodiments, the synthetic device is selected from any one of a two-sided top press, a four-sided top press, and a hinged six-sided top press, or a variant ultra-high pressure device based on a hinged six-sided top press. The difference between these presses is that they can apply high pressure in several directions. The six-sided top press can apply high pressure on the six faces of the cube at the same time, so that the sample is evenly stressed.

[0081] In some embodiments of the present application, a six-sided top large cavity press is used. In the above step S2, before synthesis, the pre-pressed embryo body needs to be assembled using a pyrophyllite mold (this process is completed in a glove box). Further, in some embodiments, the specific assembly method can be that the cylindrical blank 7 obtained after pre-pressing is placed in a hexagonal boron nitride round tube 6, and the upper and lower ends of this round tube are successively sealed with hexagonal boron nitride round tube discs; then it is placed in a carbon tube 5, and the carbon tube 5 is successively sealed with graphite sheets; then the zirconium oxide ring 4, molybdenum sheet 2 and metal plug 1 with built-in graphite column are successively added above and below, and each assembly part and between the assembly part and the sample block are interference fit, and finally placed in a pyrophyllite assembly block.

[0082] Among them, the metal plug 1, molybdenum sheet 2 and carbon tube 5 play a conductive role, heating the sample (blank 7) by applying current; the pyrophyllite 3 plays a pressure transmission role, transmitting the pressure to the internal sample through the pyrophyllite 3; the zirconia ring 4 and the hexagonal boron nitride tube 6 play a role in heat preservation and pressure maintenance.

[0083] In some embodiments of the present application, in order to obtain a purer (Li r X a )(B s Y b )(S t Z c ) crystal material, the obtained synthetic product can be lightly polished with fine sandpaper in a closed environment or protective atmosphere (for example, in a glove box) to remove trace amounts of attached boron nitride powder. The operation in the glove box is mainly to isolate water and oxygen. Generally, the water and oxygen value of the glove box is less than 0.1ppm.

[0084] In some embodiments of the present application, a solid electrolyte prepared by the above-mentioned preparation method is also provided.

[0085] The embodiment of the present application also provides a battery, comprising any one of the above-mentioned solid electrolytes. The battery using the solid electrolyte has characteristics based on the solid electrolyte.

[0086] The features and performance of the present application are further described in detail below in conjunction with the embodiments.

[0087] Example 1

[0088] This embodiment provides a method for preparing a solid electrolyte, comprising the following steps:

[0089] (1) Weigh Li with a molar ratio of 1:2:3 2S, B powder and S powder are then placed in a vacuum ball mill (this process is carried out in a glove box) for thorough ball milling at a speed of 400r / min and a grinding time of 6h; the ball-milled powder is pre-pressed into a complete cylindrical shape at a pressure of 80MPa and maintained at pressure for 3min for molding (carried out in a glove box).

[0090] (2) Assemble the high-pressure synthesis block. The assembly diagram is as follows: Figure 1 As shown. The cylindrical blank 7 obtained after pre-pressing is placed in a hexagonal boron nitride tube 6, and the upper and lower ends of the tube are sealed with hexagonal boron nitride tube discs in turn; then it is placed in a carbon tube 5, and the upper and lower ends of the carbon tube 5 are sealed with graphite sheets in turn; then the zirconia ring 4 with built-in graphite column, molybdenum sheet 2 and metal plug 1 are added in turn above and below, and each assembly part and the assembly part and the sample block are interference fit, and finally it is placed in a pyrophyllite assembly block.

[0091] Among them, the metal plug 1, molybdenum sheet 2 and carbon tube 5 play a conductive role, heating the sample (blank 7) by applying current; the pyrophyllite 3 plays a pressure transmission role, transmitting the pressure to the internal sample through the pyrophyllite 3; the zirconia ring 4 and the hexagonal boron nitride tube 6 play a role in heat preservation and pressure maintenance.

[0092] (3) placing the high-pressure synthesis block assembled in step (2) in the synthesis chamber of a six-sided top press for reaction, the synthesis temperature is 1100° C., the pressure is about 5 GPa, and the synthesis reaction time is about 60 min; after the reaction is completed, the temperature is lowered to room temperature and then the pressure is released, and the target product in the synthesis chamber is quickly taken out to obtain the target product LiBS 2 Cubic phase.

[0093] Unless otherwise specified, the remaining embodiments and comparative examples were carried out using the same high pressure synthesis block assembly method as that of embodiment 1.

[0094] Example 2

[0095] This embodiment provides a method for preparing a solid electrolyte, comprising the following steps:

[0096] (1) Weigh Li with a molar ratio of 1:2:3 2 S, B powder and S powder are then placed in a vacuum ball mill (this process is carried out in a glove box) for thorough ball milling at a speed of 400r / min and a grinding time of 6h; the ball-milled powder is pre-pressed into a complete cylindrical shape at a pressure of 80MPa and maintained at pressure for 3min for molding (carried out in a glove box).

[0097] (2) placing the cylindrical blank pre-pressed in step (1) as a reactant in a high pressure synthesis block; placing the assembled high pressure synthesis block (assembly diagram as shown in FIG. Figure 1As shown, the metal plug 1, molybdenum sheet 2 and carbon tube 5 play a conductive role, and the sample (blank 7) is heated by applying current; the pyrophyllite 3 plays a pressure transmission role, and the pressure is transmitted to the internal sample through the pyrophyllite 3; the zirconium oxide ring 4 and the hexagonal boron nitride round tube 6 play a role of heat preservation and pressure preservation. ) is placed in the synthesis chamber of the six-sided top press for reaction, the synthesis temperature is 850℃, the pressure is about 5GPa, and the synthesis reaction time is about 60min; after the reaction is completed, the temperature is cooled to room temperature and then the pressure is released, and the target product in the synthesis chamber is quickly taken out to obtain the target product LiBS 2 Four directions.

[0098] Example 3

[0099] This embodiment provides a method for preparing a solid electrolyte, comprising the following steps:

[0100] (1) Weigh Li with a molar ratio of 1:2:3 2 S, B powder and S powder are then placed in a vacuum ball mill (this process is carried out in a glove box) for thorough ball milling at a speed of 400r / min and a grinding time of 6h; the ball-milled powder is pre-pressed into a complete cylindrical shape at a pressure of 80MPa and maintained at pressure for 3min for molding (carried out in a glove box).

[0101] (2) placing the cylindrical blank pre-pressed in step (1) as a reactant in a high pressure synthesis block; placing the assembled high pressure synthesis block (assembly diagram as shown in FIG. Figure 1 As shown, the metal plug 1, molybdenum sheet 2 and carbon tube 5 play a conductive role, and the sample (blank 7) is heated by applying current; the pyrophyllite 3 plays a pressure transmission role, and the pressure is transmitted to the internal sample through the pyrophyllite 3; the zirconium oxide ring 4 and the hexagonal boron nitride tube 6 play a role of heat preservation and pressure preservation. ) is placed in the synthesis chamber of the six-sided top press for reaction, the synthesis temperature is 750℃, the pressure is about 5GPa, and the synthesis reaction time is about 60min; after the reaction is completed, the temperature is lowered to room temperature and then the pressure is released, and the target product in the synthesis chamber is quickly taken out to obtain the target product LiBS 2 Hexagonal phase.

[0102] Example 4

[0103] This embodiment provides a method for preparing a solid electrolyte, comprising the following steps:

[0104] (1) Weigh Li with a molar ratio of 1:2:3 2 S, B powder and S powder are then placed in a vacuum ball mill (this process is carried out in a glove box) for thorough ball milling at a speed of 400r / min and a grinding time of 6h; the ball-milled powder is pre-pressed into a complete cylindrical shape at a pressure of 80MPa and maintained at pressure for 3min for molding (carried out in a glove box).

[0105] (2) placing the cylindrical blank pre-pressed in step (1) as a reactant in a high pressure synthesis block; placing the assembled high pressure synthesis block (assembly diagram as shown in FIG. Figure 1 As shown, the metal plug 1, molybdenum sheet 2 and carbon tube 5 play a conductive role, and the sample (blank 7) is heated by applying current; the pyrophyllite 3 plays a pressure transmission role, and the pressure is transmitted to the internal sample through the pyrophyllite 3; the zirconium oxide ring 4 and the hexagonal boron nitride tube 6 play a role of heat preservation and pressure preservation. ) is placed in the synthesis chamber of the six-sided top press for reaction, the synthesis temperature is 650℃, the pressure is about 5GPa, and the synthesis reaction time is about 60min; after the reaction is completed, the temperature is lowered to room temperature and then the pressure is released, and the target product in the synthesis chamber is quickly taken out to obtain the target product LiBS 2 Monoclinic phase.

[0106] Example 5

[0107] This embodiment is basically the same as Embodiment 1, except that the synthesis pressure is 1 GPa.

[0108] Example 6

[0109] This embodiment is basically the same as Embodiment 1, except that the synthesis pressure is 3 GPa.

[0110] Example 7

[0111] This embodiment is substantially the same as embodiment 2, except that the synthesis time is 40 min.

[0112] Example 8

[0113] This embodiment is substantially the same as embodiment 2, except that the synthesis time is 50 min.

[0114] Example 9

[0115] This embodiment is basically the same as embodiment 1, except that in step (1), the ball mill speed is 500 r / min and the grinding time is 8 h.

[0116] Example 10

[0117] This comparative example is basically the same as Example 1, except that: in step (1), the pressure during the pre-pressing process is 100 MPa; and the pressure is maintained for 5 minutes.

[0118] Embodiment 11

[0119] This example is basically the same as Example 1, except that in step (1), the molar ratio of the substances weighed is 0.8:2:3:0.2. 2 S, B powder, S powder and Li 2 O, and the target product LiBS is obtained1.9 O 0.1 Cubic phase.

[0120] Example 12

[0121] This example is basically the same as Example 1, except that in step (1), the molar ratio of the substances weighed is 0.8:2:3:0.2. 2 S, B powder, S powder and LiI to obtain the target product Li 0.9 BS 1.9 I 0.1 Cubic phase.

[0122] Embodiment 13

[0123] This example is basically the same as Example 1, except that in step (1), the molar ratio of the substances weighed is 0.8:2:3:0.2. 2 S, B powder, S powder and LiBr to obtain the target product Li 09 BS 19 Br 01 Cubic phase.

[0124] Comparative Example 1

[0125] This comparative example is basically the same as Example 1, except that the synthesis pressure is 0.5 GPa.

[0126] Test Example 1

[0127] This test example is the target product LiBS prepared in Examples 1-4 2 The crystal structure was characterized respectively. The synthesized samples were ground in a glove box for 20 minutes, and then the samples were prepared and sealed with tape to isolate them from the air. The crystal diffraction patterns were obtained by scanning them with an X-ray diffractometer. The results are shown in the figure. Figure 2 shown.

[0128] from Figure 2 It can be seen that according to the preparation method provided in this application, four crystalline phases that cannot be synthesized under normal pressure, namely, monoclinic phase, hexagonal phase, tetragonal phase and cubic phase, can be synthesized under high pressure. In addition, it can be seen that the target product LiBS prepared in Examples 1-4 2 The crystal phase is good, the purity is as high as 99%, and it can be stably present under normal pressure. In addition, it can be seen from the XRD diagram that except for the peak of the target crystal phase, no other impurity peaks are observed, indicating that the target product prepared by the preparation method of the present application is single and has no by-products.

[0129] Test Example 2

[0130] In this test example, the ionic conductivity of the target products prepared in Examples 1-13, Comparative Examples 1 and 2 was measured. 100 mg of the product sample was placed in a mold battery with a diameter of 10 mm, and a force of 3 T was applied on a hydraulic press. The ionic conductivity at 25°C, 40°C, 60°C, 80°C, 100°C, and 120°C was obtained by testing with an electrochemical workstation. According to the formula ρ=d / (πr 2 ×R), where ρ is ionic conductivity, d is sample thickness, r is sample radius, and R is AC impedance. The ionic conductivity measurement results of the target products prepared in Examples 1-4 are as follows: Figure 3 As shown, the ionic conductivity measurement results of the target products prepared in Examples 1-13, Comparative Example 1 and Comparative Example 2 are recorded in Table 1.

[0131] Table 1

[0132]

[0133]

[0134] It can be seen from Table 1 that the ionic conductivity of the cubic phase is the highest and the ionic conductivity is good. The ionic conductivity of the cubic phase at 25 °C is 1.33×10 -4 S / cm, the ionic conductivity of the tetragonal phase at 25°C is 9.7×10 -6 S / cm, and the ionic conductivity of the hexagonal phase at 25°C is 4.82×10 -7 S / cm, the ionic conductivity of the monoclinic phase at 25°C is 4.84×10 -7 S / cm.

[0135] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.

Claims

1. A solid electrolyte, characterized in that: Its general chemical formula is shown in formula (I): (Li r )(B s )(S t Z c ) Formula (I) The crystal form of the compound represented by formula (I) is any one of cubic phase, tetragonal phase, hexagonal phase and monoclinic phase; The method for preparing the solid electrolyte comprises the following steps: S1. The initial raw materials are mixed and then ground and pre-pressed to obtain an embryo; S2. The embryo in step S1 is synthesized at 1-5Gpa and above 650°C to obtain the solid electrolyte, whose general chemical formula is (Li r )(B s )(S t Z c ); the synthesis temperature is 650-1100°C; The initial raw materials include a lithium source, a sulfur source, and a boron source, wherein the lithium source includes one or more of lithium sulfide, lithium iodide, lithium bromide, and lithium oxide; the sulfur source includes sulfur powder; and the boron source includes boron powder; Wherein, Z is selected from any one of O, Se, F, Cl, Br and I; the anion valence of Z is -p; r, s, t and c respectively satisfy the following conditions: 0≤c≤1, and t+c=2; r+3s=2t+pc.

2. The solid electrolyte according to claim 1, characterized in that c=0, and the chemical formula of the solid electrolyte is LiBS2.

3. The solid electrolyte according to claim 1, characterized in that The grinding conditions include: grinding speed of 400-500r / min, grinding time of 6-10h; And / or, the pre-pressing conditions include: a pressure of 60-100 MPa and a holding time of 1-5 min.

4. The solid electrolyte according to claim 3, characterized in that The grinding time is 6-8h; and / or the pressure is 80MPa, and the pressure holding time is 3min.

5. The solid electrolyte according to any one of claims 1 to 4, characterized in that The synthesis temperature is 650-1100°C.

6. The solid electrolyte according to claim 5, characterized in that The synthesis temperature is selected from any one of ad: a. The synthesis temperature is 1000-1100°C, wherein the corresponding crystal form of the compound represented by formula (I) is cubic phase; b. The synthesis temperature is 850-1000°C, wherein the corresponding crystal form of the compound represented by formula (I) is tetragonal; c. The synthesis temperature is 750-800°C, wherein the corresponding crystal form of the compound represented by formula (I) is hexagonal; d. The synthesis temperature is 650-700°C, wherein the corresponding crystal form of the compound represented by formula (I) is monoclinic.

7. The solid electrolyte according to claim 6, characterized in that The synthesis time is 40-60 min.

8. A battery, characterized in that: The invention comprises the solid electrolyte according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Solid electrolyte and preparation method and application thereof

    CN114784369A

  • Novel lithium metal sulfides as lithium super-ionic conductors

    US20200099093A1

  • Cell containing alkali metal anode, cathode and alkali metal-metal-chalcogenide compound solid electrolyte

    US4208474A